Highly interactive kink solutions - Gomes, Adalto R.; Menezes, Romualdo R.; Oliveira, Joana (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
In this work we present a new class of real scalar field models admitting strongly interactive kink solutions. Instead of the usual exponential asymptotic behavior these topological solutions exhibit a power-law one. We investigate the interaction force between a pair of kink/antikink solutions both analytically and numerically, by integrating the time dependent field equations of the model. Furthermore, working within the first-order framework, we analyze the linear stability of these solutions. The stability analysis leads to Schödinger-like equations with potentials which, despite admitting no bound states, lead to strong resonance peaks. We argue that these properties are important for some possible physical applications.